2015
DOI: 10.1155/2015/126858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Docking Target Functions by the Comprehensive Investigation of Protein-Ligand Energy Minima

Abstract: The adequate choice of the docking target function impacts the accuracy of the ligand positioning as well as the accuracy of the protein-ligand binding energy calculation. To evaluate a docking target function we compared positions of its minima with the experimentally known pose of the ligand in the protein active site. We evaluated five docking target functions based on either the MMFF94 force field or the PM7 quantum-chemical method with or without implicit solvent models: PCM, COSMO, and SGB. Each function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 29 publications
1
59
0
4
Order By: Relevance
“…However, realization of mobility of the target protein atoms in the docking procedure needs adoption the new docking 102 approach: instead of the traditional docking technique using the preliminary calculated energy grid of probe ligand atoms in the eld of the target protein (see, for example, SOL [46]) the straightforward docking procedure must be used. In this docking procedure the protein-ligand energy is calculated directly in the frame of the given force eld for any ligand pose in the target protein active site (see, for example FLM [7,8] and SOL-T [22]). But such approach demands much more computational expenses, especially when the target protein atoms are moveable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, realization of mobility of the target protein atoms in the docking procedure needs adoption the new docking 102 approach: instead of the traditional docking technique using the preliminary calculated energy grid of probe ligand atoms in the eld of the target protein (see, for example, SOL [46]) the straightforward docking procedure must be used. In this docking procedure the protein-ligand energy is calculated directly in the frame of the given force eld for any ligand pose in the target protein active site (see, for example FLM [7,8] and SOL-T [22]). But such approach demands much more computational expenses, especially when the target protein atoms are moveable.…”
Section: Resultsmentioning
confidence: 99%
“…The APLITE program [6,8] adds hydrogen atoms according to the standard protonation states of amino acids at pH = 7,4. Protonation states of hisitidines were selected by the comparison of hydrogen atoms electrochemical potentials in "HD1" and "HE2" positions.…”
Section: Hydrogen Atoms Incorporation Into a Target Protein And A Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable improvements on docking have been made when molecular dynamics are used to prepare the structures of molecular targets, for instance, to conduct energy minimization and assign charges (Alonso, Bliznyuk & Gready, 2006;Uehara & Tanaka, 2017). For ligand preparation, methods that have improved docking results include: optimization using semiempiric charges (Adeniyi & Soliman, 2017;Marzaro et al, 2013;Oferkin et al, 2015;Xu & Lill, 2013), COSMO solvation (Oferkin et al, 2015), molecular mechanics Poison-Boltzmann/ surface area (Halperin, Wolfson & Nussinov, 2002), and force field optimization (Zoete, Cuendet, Grosdidier & Michielin, 2011). Moreover, it has been shown that forcefield optimization with implicit solvent is comparable to advanced semi-empirical methods (e.g.…”
Section: Pose Vs Scoringmentioning
confidence: 99%
“…Hence, the first step is the identification of key water molecules and their contribution (Kumar & Zhang, 2013). Methods that have advanced the correct representation of water molecules in proteins include: free energy perturbation methods (Jorgensen & Thomas, 2008), Monte Carlo probability (Parikh & Kellogg, 2014), molecular dynamics of water on the binding site (as implemented by Schrödinger (Kumar & Zhang, 2013;Waszkowycz, Clark & Gancia, 2011)), water displacement as implemented by PLANTS (Korb, Stützle & Exner, 2009), "Attachment" of water molecules to ligands as additional torsions (Lie, Thomsen, Pedersen, Schiøtt & Christensen, 2011), QM/ MM hybrid methods (Xu & Lill, 2013), COSMO solvation, and semi-empirical charges for ligands (Oferkin et al, 2015). Additional methods are "hydrated docking" scripts for Autodock (Forli et al, 2016), protein-centric and ligand centric hydration as implemented by Rossetta (Lemmon & Meiler, 2013), Water docking using Vina (Ross, Morris & Biggin, 2012;Sridhar et al, 2017), WScore (Murphy et al, 2016), and grid inhomogeneous solvation theory applied by Autodock (Uehara & Tanaka, 2016).…”
Section: Water Solvation and Dockingmentioning
confidence: 99%